Organización contable y tributaria en la microempresa Nahyssa distribuciones de la ciudad de Loja. Periodo del 01 de octubre al 31 de diciembre del 2021. - Salinas Yaguana, Nahyssa Dayanna (2022)
The curricular integration work called ACCOUNTING AND TAX ORGANIZATION IN THE MICROENTERPRISE "NAHYSSA DISTRIBUCIONES" OF THE CITY OF LOJA, PERIOD FROM OCTOBER 01 TO DECEMBER 31, 2021, prepared in accordance with the Academic Regime Regulations of the Universidad Nacional de Loja, prior Obtaining the degree of Bachelor of Accounting and Auditing, allowed to know the economic and financial situation of the microenterprise so that in this way the corresponding decisions can be made. In order to comply with the objectives set out in the project for the curricular integration work, information was collected about the assets, values, rights and obligations of the microenterprise at the beginning of the accounting period in order to establish the Initial Inventory and the Initial Statement of Situation in which $154,962.90 in Assets, $23,876.73 in Liabilities and therefore $131,086.17 in Equity were obtained, which allowed the preparation of the Chart of Accounts ordered and codified according to the requirements and obligations of the business and the Accounts Manual describing the dynamics, balance of the accounting accounts and the definition compiled from different physical and electronic sources; After having obtained the Assets, Liabilities and Equity of the business, the source documents were collected to carry out the memorandum of operations. In compliance with the second objective, the main accounting formats were designed, such as the Daily Book, General Ledger, Trial Balance and Financial Statements; and, the auxiliary formats in relation to purchases, sales, accounts receivable, accounts payable and other formats necessary to synthesize the information and facilitate the control of income and expenses of merchandise, credits made to customers, obligations with suppliers and other information necessary for the registration of commercial operations. For the development of the accounting process, the operations were recorded in the daily book through the multiple account system or periodic inventory, the transactions presented in a chronological, orderly and systematic manner in the memorandum of operations were taken into account, which allowed that the accounting entries of the economic movements made in the period be transferred to the general ledger and subsequently to the trial balance; the adjustments corresponding to the regulation of the merchandise account, depreciation, consumption and provisions were made; to then verify the balances in the worksheet, concluding with the preparation of the financial statements and the explanatory notes that provide information on the resources it has, the results it has obtained and the cash inflows and outflows made in the year economic, given that the Statement of Financial Position shows $164,333.66 in assets, $31,121.28 in liabilities, $133,212.38 in equity; the Income Statement presents $2,126.21 in profit for the year for the company in the period from October 1 to December 31, 2021; and, the Cash Flow Statement reveals a positive balance of $7,951.71. Therefore, it was possible to verify that the accounting and tax organization in the microenterprise has allowed establishing an effective registration and control of commercial operations, in addition to helping to optimize business resources, it will make it possible to obtain information regarding the economic situation and of the business for making timely decisions and corrective measures that contribute to the achievement of the business objectives and goals set.